Sunday

April 20, 2014

April 20, 2014

Posted by **Jayden Haddy** on Saturday, August 17, 2013 at 5:59am.

- maths -
**Naruto**, Saturday, August 17, 2013 at 6:28amsum = p

product = q

let a & b the roots

a + b = p

ab = q

since a & b are consecutive integers (i.e. b = a+1):

2a + 1 = p

a^2 + a = q

substitute.

p^2 - 4q -1 = 0

4a^2 + 4a + 1 - 4a^2 + 4a - 1 = 0

indeed,

0 = 0

**Related Questions**

maths - If the roots of the quadratic equation 4x^2 + px +5 = 0 are a and a+2, ...

Algebra - The equation x^2+px+q=0, q cannot be equal to 0, has two unequal roots...

Math - The equation x^2+px+q=0, q cannot be equal to 0, has two unequal roots ...

Adv algebra - The equation x^2+px+q=0, q cannot be equal to 0, has two unequal ...

Math - Let f(x)= px^5 + qx^4 + rx^3 + sx^2 + tx + u be a polynomial such that f(...

Math - Suppose p and q are odd integers. (a) Show that the quadratic equation x2...

further mathematics - The roots of the eqn, x^4 + px^3 + qx^2 + rx + s = 0 where...

Maths - Is given a function: f(x)=x2 + px + q Prove that: f(x+1) + f(x-1)= 2+2 f...

very complicated maths - Hey guys, need some help with a question ive been stuck...

math - Prove that if p, q, r and s are odd integers, then the equation x^10 + px...